Conversion of syngas into light olefins over bifunctional ZnCeZrO/SAPO-34 catalysts: regulation of the surface oxygen vacancy concentration and its relation to the catalytic performance. Issue 1 (16th November 2020) - Luo, Yaoya; Wang, Sen; Guo, Shujia; Yuan, Kai; Wang, Hao; Dong, Mei; Qin, Zhangfeng; Fan, Weibin; Wang, Jianguo
Abstract : Surface oxygen vacancies can improve the formation of methanol intermediates and promote their evolution into olefin products for syngas-to-olefins over Zn0.5 CeZrO x /SAPO-34. Abstract : The surface oxygen vacancy concentration on ZnCeZrO composite oxides was finely tuned through modulating the preparation method and altering the precursor calcination temperature; the effect of the surface oxygen vacancy concentration on the performance of bifunctional ZnCeZrO/SAPO-34 catalysts in the direct conversion of syngas into light olefins (STO) was then investigated. The results indicate that the surface oxygen vacancy concentration of Zn0.5 CeZrO x composite oxides can be markedly elevated by preparation through a sol–gel method with glucose as the complexing agent and calcination at 500 °C; a higher surface oxygen vacancy concentration leads to a higher space–time yield of methanol for syngas conversion over the Zn0.5 CeZrO x  oxide. When combined with SAPO-34 molecular sieves, the bifunctional Zn0.5 CeZrO x /SAPO-34 catalyst with high surface oxygen vacancy concentration also exhibits a high space–time yield of light olefins (ethene to butenes) in the synthesis of olefins directly from syngas. With the help of in situ DRIFTS, it can be concluded that the surface oxygen vacancies on the ZnCeZrO oxide play an important role in the catalytic conversion of syngas. The abundant surface oxygen vacancies on Zn0.5 CeZrO x can improve the formation of methanol-related intermediates from the syngas over the Zn0.5 CeZrO x moiety, promote the evolution of these intermediates into the olefin products over the SAPO-34 moiety, and then enhance the overall capacity of the bifunctional Zn0.5 CeZrO x /SAPO-34 composite catalyst in STO.